Using SOA for development of information system ‘Smart city’ - Duravkin, Evgen (Видавництво Львівської політехніки, 2010)
An approach to building information system of the smart city, based on the technology of SOA is discussed in the paper. The proposed approach will improve the manageability of the system, increase its speed and reliability, as well as no less important to provide security.
Keywords: Smart city; Service-Oriented Architecture; network protocol